Mesenchymal stem cells in tumor microenvironment: drivers of bladder cancer progression through mitochondrial dynamics and energy production - Yang, Enguang; Jing, Suoshi; Wang, Fang; Wang, Hanzhang; Fu, Shengjun; Yang, Li; Tian, Junqiang; Golijanin, Dragan J.; El-Deiry, Wafik S.; Cheng, Liang; Wang, Zhiping (Cell death & disease, 2024)
Mesenchymal stem cells (MSCs) in tumor microenvironment (TME) are crucial for the initiation, development, and metastasis of cancer. The impact and mechanism of MSCs on bladder cancer are uncertain. Here we analyzed 205 patient samples to explore the relationships between tumor-stroma ratio and clinicopathological features. A co-culture model and nude mouse transplantation were used to explore the biological roles and molecular mechanisms of MSCs on bladder cancer cells. We found that a high tumor-stroma ratio was significantly associated with a larger tumor size and higher T stage, pathological grade, number of vascular invasions, and poor overall survival. MSCs in TME promoted the ability of bladder cancer cells to proliferate, migrate, and invade in vitro and in vivo. Next, we demonstrated that MSCs enhance mitochondrial autophagy and mitochondrial biogenesis of bladder cancer cells, and increase energy production, thereby promoting bladder cancer cell progression. Kynurenine (Kyn) produced by MSCs could enhance mitochondrial function by activating the AMPK pathway. IDO1 inhibitor could reverse the tumor‑promoting effects of MSCs in vitro and in vivo. Our results demonstrated that tryptophan metabolites Kyn of MSCs in TME could enhance mitochondrial function by activating the AMPK pathway, thereby promoting bladder cancer cell progression.